Antioxidant activities of oligostilbenoids from the stem bark of Dipterocarpus verrucosus, Dipterocarpus crinitus and Dipterocarpus cornutus - Zuraida Wan Mohd Zain, Wan; Ahmat, Norizan; Puteh Osman, Che (International Journal of Engineering and Technology, 2018)
Resveratrol, a stilbene-based polyphenol, is known to be substantially beneficial for human health because of its significant roles as antioxidant agents. Its oligomers received a considerable chemical and biological interest because of their structural complexity as well as their wide array of bioactivities role and function that includes as an antioxidative agent. Based on previous report, only 17 oligomers from Dipterocapaceae have been studied for their antioxidant and other activities. In an attempt to explore new antioxidant leads, the stem bark of Dipterocarpus from Dipterocarpaceae family were extracted and purified to give 14 oligostilbenes. The structures of the compounds were determined by comprehensive analysis of spectroscopic data including UV, IR, MS and NMR after purification of individual compounds through a combination of chromatographic methods. The antioxidant activity was measured using four methods (Total Phenolic Content, DPPH, FTC and TBA). Fourteen compounds were screened for DPPH activity while only major compounds were screened using FTC and TBA methods in order to investigate the possible correlation between both mechanisms. The crude extracts showed high percent inhibition in TPC, FTC, TBA and DPPH methods. The TPC values for the crude extracts are within a range of 331.54 – 482.31 mg/g GAE. In DPPH radical scavenging activity, the crudes displayed lower radical scavenging activity as compared to BHT and ascorbic acid. Nevertheless, D. verrucosus and D. cronutus demonstrated a significant free radical scavenging ability with IC50 values of 80 and 210 µg/ml, respectively. Both species also showed low absorbance values, which indicated a high level of antioxidant activity in FTC method. D. verrucosus, D. cornutus and D. crinitus extracts exhibited antioxidant potential in TBA method with percent inhibition of 88.64 %, 99.13 % and 95.02 %, respectively, as compared to vitamin E which has a percent inhibition of 83.23 % at a final concentration of 0.02% w/v. Evaluation on compounds indicated that resveratrol, diptoindonesin E, 4-methoxygallocatecatechin, ampelopsin A and scopoletin possessed IC50 values between 75-450 µg/mL in the DPPH assay. The results suggest that oligomer resveratrol from Dipterocarpus are potential sources of natural antioxidants.